Building Children's Spiritual Foundations: A Study on the Implementation of Islamic Religious Education in Muslim Families - Nadia Fitria Utami (Sufiya Journal of Islamic Studies, 2024)
This study aims to examine the implementation of Islamic religious education within Muslim families as a foundation for the development of children's spirituality. Utilizing a qualitative approach with a field study method, the research was conducted in the village of Pringgan Paya Pasir Marelan. Data were collected through observation, in-depth interviews, and documentation involving seven randomly selected Muslim families. The findings reveal that Islamic education in the family is implemented through four main aspects: faith (ʿaqīdah), ethics (akhlāq), worship (ʿibādah), and social values, primarily through habituation and parental role modeling. However, the implementation faces several challenges, including limited religious knowledge among parents, reduced family interaction time due to economic demands, and the uncontrolled influence of digital media. These findings highlight the need to strengthen the family’s role in religious education through structural and collaborative support, ensuring that Islamic values are internalized from an early age. This research contributes to the discourse on family-based Islamic education and offers practical implications for nurturing a devout Muslim generation in the modern era.